2008
DOI: 10.1002/cbdv.200890155
|View full text |Cite
|
Sign up to set email alerts
|

Marine Drugs – Macrolactins

Abstract: The increasing demands for new lead compounds in pharmaceutical and agrochemical industries have driven scientists to search for new bioactive natural products. Marine microorganisms are rich sources of novel, bioactive secondary metabolites, and have attracted much attention of chemists, pharmacologists, and molecular biologists. This mini-review mainly focuses on macrolactins, a group of 24-membered lactone marine natural products, aiming at giving an overview on their sources, structures, biological activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
16
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 24 publications
2
16
0
Order By: Relevance
“…Marine Bacillus species are well known for producing antimicrobial macrolactin A, a 24-membered macrolactone, and their derivatives. 20 Macrolactin A showed potent antibacterial activity against Staphylococcus aureus and Bacillus subtilis in standard 'disc diffusion assay' at a concentration of 5 and 20 mg per disc, 10 respectively. The position of hydroxy groups in macrolactone ring is important for antimicrobial activity of macrolactins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Marine Bacillus species are well known for producing antimicrobial macrolactin A, a 24-membered macrolactone, and their derivatives. 20 Macrolactin A showed potent antibacterial activity against Staphylococcus aureus and Bacillus subtilis in standard 'disc diffusion assay' at a concentration of 5 and 20 mg per disc, 10 respectively. The position of hydroxy groups in macrolactone ring is important for antimicrobial activity of macrolactins.…”
Section: Discussionmentioning
confidence: 99%
“…22 New macrolactins X-Z (1-3) showed antimicrobial activity comparable to the literature values, as there were no major structural differences among new macrolactins and published macrolactins. 20 By comparing the antibacterial activity among different fatty acids, it has been shown that unsaturated and hydroxy fatty acids (4-6) showed better antibacterial activity compared with saturated fatty acids. 23,24 Although there are several reports regarding the mode of action of long-chain unsaturated fatty acids, the precise mechanism for the antimicrobial activity is not clearly understood.…”
Section: Discussionmentioning
confidence: 99%
“…Compounds 1-3 exhibit a minimum inhibitory concentration (MIC) of 0.16 μM against Bacillus subtilis and Escherichia coli in a standard in vitro broth dilution assay. 6 Their MICs against Saccharomyces cerevisiae were 0.16, 0.02, and 0.16 μM, respectively. As a continuation of our group's interest in the synthesis of tetrahydropyran-containing molecules of complex architecture, the bioactivity of macrolactin 3 prompted us to undertake its synthesis.…”
Section: Introductionmentioning
confidence: 96%
“…First isolated from a deep-sea marine bacterium, macrolactins are mostly secondary metabolites of marine microorganisms (1,2). At least 18 isolated macrolactins have been reported, including some recent discoveries (2,3).…”
mentioning
confidence: 99%
“…First isolated from a deep-sea marine bacterium, macrolactins are mostly secondary metabolites of marine microorganisms (1,2). At least 18 isolated macrolactins have been reported, including some recent discoveries (2,3). Five of these macrolactins were generated by Bacillus polyfermenticus KJS-2 (BP-2) and were identified as macrolactin A (MA), 7-Omalonyl macrolactin A, 7-O-succinyl macrolactin A (SMA), macrolactin E, and macrolactin F (4).…”
mentioning
confidence: 99%